Preferences for Energy Efficiency vs. Renewables: How Much Does a Ton of CO₂ Emissions Cost? - Anna Alberini; Andrea Bigano; Milan Šcasný; Iva Zverinová (Fondazione Eni Enrico Mattei (FEEM), 2016)
Concerns about climate change are growing, and so is the demand for information about the costs and benefits of mitigating greenhouse gas emissions. This paper seeks to estimate the benefits of climate change mitigation, as measured by the public's willingness to pay for such policies. We investigate the preferences of Italian and Czech households towards climate change mitigation policy options directly related to residential energy use. We use discrete choice experiments, which are administered in a standardized fashion to representative samples in the two countries through computer-assisted web interviews. The willingness to pay per ton of CO2 emissions avoided is exteuro132 Euro for the Italians and 94 Euro for the Czech respondents (at 2014 purchasing power parity). We find evidence of considerable heterogeneity in WTP driven by income. The two samples differ in their “domestic” income elasticities of WTP, but comparison across the two countries suggests an income elasticity of WTP of one.
Keywords: Q41; Q48; Q54; Q51; 330; Energy-efficiency Incentives; Stated Preferences; CO2 Emissions Reductions; CO2 Mitigation Policies; Conjoint Choice Experiments; WTP for CO2 Emissions Reductions